1999
DOI: 10.1046/j.1469-8137.1999.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth response of grassland species to ozone in relation to soil moisture condition and plant strategy

Abstract: Plant species typical of semi-natural grasslands were tested for their sensitivity to long-term ozone effects on growth under two irrigation regimes, and the relationship between ozone sensitivity, relative growth rate, and plant strategy was analysed. Individuals of 24 grasses, herbs and legumes were grown in pots and exposed for two seasons to four levels of ozone in open-top chambers : (a) CF, charcoal-filtered air, (b) CFAA, charcoal-filtered air plus ozone to match ambient levels, (c) CFj, charcoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 26 publications
3
30
2
Order By: Relevance
“…When Species and\or g s were used, other inputs were of little or no importance. Removing Species and g s as inputs revealed that R does not become the most important variable, in contrast with what could be expected from the observed positive correlation between the reduction in growth by O $ and R (Reiling & Davison, 1992 ;Bungener et al, 1999). When plant-specific parameters are not included in the model, VPD 5 days appears to be the most important variable, confirming the results of the analysis of data for T. repens obtained in ambient air (Benton et al 1996).…”
Section: Artificial Neuron Network Model Analysiscontrasting
confidence: 51%
See 3 more Smart Citations
“…When Species and\or g s were used, other inputs were of little or no importance. Removing Species and g s as inputs revealed that R does not become the most important variable, in contrast with what could be expected from the observed positive correlation between the reduction in growth by O $ and R (Reiling & Davison, 1992 ;Bungener et al, 1999). When plant-specific parameters are not included in the model, VPD 5 days appears to be the most important variable, confirming the results of the analysis of data for T. repens obtained in ambient air (Benton et al 1996).…”
Section: Artificial Neuron Network Model Analysiscontrasting
confidence: 51%
“…Injured and healthy leaves were separated and counted at each harvest. Further details of the harvesting procedure are given in Bungener et al (1999). In the course of each growth period, the date of first appearance of injured leaves was recorded for each plant species in each treatment, and the type of injury was noted.…”
Section: Harvests and Assessment Of Visible Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…When grown under shade cloth at 24% of full light intensity, plants devoted energy to reproduction at the expense of root growth and production of late-season leaves (Boutin and Morisset 1988). Bungener et al (1999) found that L. vulgare was sensitive to ozone concentrations of double the ambient level, exhibiting decreased biomass in the first year of growth. In contrast, Mortensen and Nilsen (1992) found that L. vulgare biomass did not decrease with exposure to enhanced ozone levels, but exposed plants did exhibit chlorosis.…”
Section: Growth and Developmentmentioning
confidence: 99%